STRATEGIC SPEECH ACTS ON TIKTOK LIVE: : (Campaign Tactics on Presidential Canidate 01, 02, 03 in Indonesia’s 2024 Election) - Dewi Kurniawati; Nurul Intan Pratiwi; Farizka Humolungo; Yoyok Sabar Waluyo; Mauli Denil; Hana Khalisa Zahra; Farsya Ramadhina Hati Pahlevi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study focuses on the campaign of Candidate Pairs No. 01, 02, and 03 during the 2024 Indonesian Presidential Election in TikTok Live. This analysis examines on how public communication through TikTok Live mobilizes empathy, using speech act theory to examine the social functions of these texts. The campaign is targeting millennial and Generation Z that’s why the media used reliance on social media, that caters to the new communication way of these younger generations. The analysis is grounded in Austin’s (1962) speech act theory, focusing on Locution and Illocution, completed by Searle’s (1979) categories such as Assertive, Directive, Commissure, Expressive, and Declarative. Focusing on the strategic speech acts by comparing the persuasive speech acts used by the candidate pairs. Previous studies on speech act analysis in champaign communication strategy only focus on speech and poster. Ismail, F. (2013) focus on pragmatis study on Jokowi’s speech , while Ulum et.all (2018) compares Trumpt and Clinton speech strategy and focus on commisive analaysis and Ali et.all (2022)studied on pragmatic in campaign poster. This study significantly diferent in case that speech act strategies are identified on politiciants’ camphaign in TikTok Live. A social media that newly become trend in public communication. The findings shows that Live TikTok speech act shows different communication strategy comparing to formal interview that shows 90% assertive with low commisive and declarative. This phenomenon is very unique since in conventional campaign, most utterances are representing commisive and declarative to gain support. It offers new insights into public communication strategies in the digital era. The research uses a qualitative method with a descriptive analysis approach, employing content analysis and focus group discussions with pragmatics and psychology experts. Reader and listener motivation will also be analysed through the lens of empathy psychology.